1998
DOI: 10.1200/jco.1998.16.2.551
|View full text |Cite
|
Sign up to set email alerts
|

Error rates in clinical radiotherapy.

Abstract: When modern automated error-minimization methods are used along with nonpunitive error reporting systems, clinical radiotherapy seems to be highly safe. Formal error analysis studies may allow the rational design of prevention strategies that are attuned to the frequency, seriousness, and antecedent causes of many classes of potential radiotherapy errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 15 publications
3
52
0
Order By: Relevance
“…The three studies that are most similar to ours are those by Macklis et al (25)., Valli et al (26), and Yeung et al (27) Macklis et al (25) report on a prospective study of 1 year of treatment in one institution. They examined planning and treatment delivery with their study focus being the most like the focus of ours.…”
Section: Discussionsupporting
confidence: 78%
“…The three studies that are most similar to ours are those by Macklis et al (25)., Valli et al (26), and Yeung et al (27) Macklis et al (25) report on a prospective study of 1 year of treatment in one institution. They examined planning and treatment delivery with their study focus being the most like the focus of ours.…”
Section: Discussionsupporting
confidence: 78%
“…The first identified is data entry. 6,7,9,10,12,13 Five publications showed that as new information was entered into an electronic information system, deviation rates increased. 6,9 -12 A second major source of deviation occurs when new technologies are introduced into the clinic, 6,9 -11 presumably as a result of the personnel learning curve associated with the new technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Macklis et al 16 collected data for incidents where some part of the treatment had been carried out erroneously in comparison with the prescribed dose and method of delivery. Incident reports were collated and errors were categorised as mentioned in an above section.…”
Section: Errorsmentioning
confidence: 99%
“…Other authors approached this matter differently. Macklis et al 16 utilised a stratification of errors into three risk levels. Level 1 errors were dose discrepancies that resulted in less than 5% overall calculated change in dose to the target volume over the whole course, whereas level 2 errors would either imply more than a 5% change, a clinically detectable increase in acute radiation toxicity caused by the error, or a systematic calculation or operational systems error.…”
Section: Severity-classification Of Incidentsmentioning
confidence: 99%